EXPERT WRITING: SCAFFOLDING INFORMATIONAL WRITING USING FAMILIAR TOPICS: SCAFFOLDING INFORMATIONAL WRITING USING FAMILIAR TOPICS - Grove, Darlene Young (fólio - Revista de Letras, 2018)
This article describes Expert Writing, a strategy to support English language learners and others in organization and idea development in informational writing. English language learners often struggle with idea development, because they lack sufficient vocabulary to construct expanded sentences and paragraphs. Expert Writing enables students to draw on topics they already know well in order to develop an informational writing piece. Students choose a topic on which they consider themselves “experts” and then “teach” about their topic to peers. This oral rehearsal gives students an audience and encourages them to think about questions a reader might have. During this step, students develop “important ideas” about the topic, which help students structure their writing as main ideas that are developed into paragraphs. Students also create “glossary words,” which become a roadmap for organizing paragraphs around the main idea.